2020
DOI: 10.1016/j.actamat.2020.03.045
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic domain-twin boundary interactions in Ni–Mn–Ga

Abstract: The stress required for the propagation of twin boundaries in a sample with fine twins increases monotonically with ongoing deformation. In contrast, for samples with a single twin boundary, the stress exhibits a plateau over the entire twinning deformation range. We evaluate the twin boundary and magnetic domain boundary interactions for increasing twin densities. As the twinned regions get finer, these interaction regions result in additional magnetic domains that form magnetoelastic defects with high magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…Such stored disconnections lead to magnetoelastic properties as opposed to magnetoplastic properties [40,97]. Veligatla et al further suggested that increased twin density introduce magnetoelastic defects, which leads to hardening [98]. The increased magnetoelasticity causes more elastic deformations, such as the curvature of the micropeened element compared to that of the polished element, in Figure 6-5b.…”
Section: Resultsmentioning
confidence: 99%
“…Such stored disconnections lead to magnetoelastic properties as opposed to magnetoplastic properties [40,97]. Veligatla et al further suggested that increased twin density introduce magnetoelastic defects, which leads to hardening [98]. The increased magnetoelasticity causes more elastic deformations, such as the curvature of the micropeened element compared to that of the polished element, in Figure 6-5b.…”
Section: Resultsmentioning
confidence: 99%